Victimological barriers in elderly people to physical education in public space - T.P. Budyakova; G.V. Baturkina (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify victimological barriers to physical education among pre-retirees, working and non-working pensioners. Methods and structure of the study. A structured interview was used as a research method. The participants of the scientific work were 60 elderly people in the status of pre-pensioners, working and non-working pensioners. Only those respondents were selected who, for various reasons, refused to participate in the physical education part of the Active Longevity program, most of them attended only one lesson. Results and conclusions. Victimological barriers significant for each status group were identified. For pre-retirees, such barriers were personal unwillingness to relate themselves to the image of an elderly person and personal rejection of the very status of classes for the elderly. For non-working pensioners, the main barriers were physical barriers caused by disability or the technology of conducting classes. Working pensioners perceived as discrimination the regulated time of classes, which coincided with their work schedule. For all groups of respondents, a significant victimological reason was the lack of coordination of the work of the organizers, who did not pay attention to the individual needs of people with different psychological and cultural attitudes, which was perceived as disrespect for the individual.